Bidirectional Mendelian randomization analysis and systematic meta-analysis of causal relationships between hepatocellular carcinoma and non-alcoholic fatty liver disease - Tielong Zhao; Yanglieguang Lou (Discover Oncology)
Abstract Background The causal relationships between hepatocellular carcinoma (HCC) and non-alcoholic fatty liver disease (NAFLD) remain unclear. This study investigated bidirectional causality between HCC and NAFLD using Mendelian randomization, and evaluated liver-related mortality risk in NAFLD patients through meta-analysis. Methods We performed bidirectional two-sample Mendelian randomization using genome-wide association study data (775 HCC cases, 1,332 controls; 8,434 NAFLD cases, 770,180 controls). Multiple analytical methods included inverse variance weighted, MR-Egger, and weighted median approaches. Meta-analysis included 8 studies with 577,921 participants examining liver-related mortality in NAFLD versus non-NAFLD populations. Results Mendelian randomization analysis revealed no significant causal relationships between HCC and NAFLD in either direction, with effect estimates consistently clustering around zero across all methods. Meta-analysis demonstrated significantly increased liver-related mortality risk in NAFLD patients (HR = 3.99, 95% CI: 2.11–7.55, P < 0.0001) with substantial heterogeneity (I² = 92.9%). Conclusion This study provides evidence against strong bidirectional causal relationships between genetic predisposition to HCC and NAFLD. However, NAFLD patients show a four-fold increased risk of liver-related mortality, highlighting the clinical importance of NAFLD as a predictor of adverse liver outcomes.